High quality of mortar with marble waste aggregate - Barbosa, Maria Teresa Gomes; Santos, White José dos; Coura, Claudia Valéria Gávio (Ambiente Construído, 2018)
<span style="font-family: ’Times New Roman’,serif; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="IT">The use of industrial waste has raised great interest regarding its potential of contributing both to the reduction of costs and to sustainable development. In this context, there has been an increasingly high number of studies addressing the use of alternative materials in the construction industry, especially when considering the difficulty in obtaining building materials near urban centers, which results in an increase in the final price due to transportation costs. This research has characterized and evaluated the use of crushed marble waste to replace natural sand in the production of mortar. Many admixtures of mortar were subject to research regarding their physical and mechanical properties. It has been concluded that mortars produced with sand made of crushed marble waste have improved mechanical properties when compared to traditional mortar.